Congédiement illégal — Une mise-à-pied est-elle un congédiement au sens de la loi ?

(untitled) (Département des relations industrielles de l’Université Laval, 1962)
SummaryAn employee who is laid off is dismissed in the sense of Sections 21a) ff. A lay-off for union activities is a mischief that the legislator intended to suppress by the said enactment. To decide otherwise would be to open the door to an unscrupulous employer, who in the guise of a lay-off, would effectively dismiss an employee, thereby indirectly achieving the illegal purpose which is directly forbidden to him by law.Jean-Paul Duhamel, requérant, vs Glo-Hill Cutlery Co. Ltd., intimée; M. le juge Allan B. Gold, vice-président; M. J.-Eucher Corbeil et Me Claude Lavery, commissaires; Commission des Relations ouvrières de Québec, D-272, Montréal, 19 mars 1962; Me René Beaudry et M. J.-J. Desroches, pour le requérant; Me Laurence Marks, pour l'intimée.